2005
DOI: 10.1083/jcb.200503155
|View full text |Cite
|
Sign up to set email alerts
|

α4β1-dependent adhesion strengthening under mechanical strain is regulated by paxillin association with the α4-cytoplasmic domain

Abstract: The capacity of integrins to mediate adhesiveness is modulated by their cytoplasmic associations. In this study, we describe a novel mechanism by which α4-integrin adhesiveness is regulated by the cytoskeletal adaptor paxillin. A mutation of the α4 tail that disrupts paxillin binding, α4(Y991A), reduced talin association to the α4β1 heterodimer, impaired integrin anchorage to the cytoskeleton, and suppressed α4β1-dependent capture and adhesion strengthening of Jurkat T cells to VCAM-1 under shear stress. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 47 publications
3
68
0
4
Order By: Relevance
“…Specific cytoskeletal partners of integrins may therefore regulate not only the affinity and clustering states of their integrin targets but also the efficiency by which an integrin occupied with ligand can strengthen its bond under the influence of external forces. In support of this possibility, we recently showed that the adhesive activity under shear of the key immune cell integrin, VLA-4, is modulated by an ␣ 4 cytoplasmic association with paxillin, without any noticeable changes in its affinity, clustering, or binding avidity to VCAM-1 2 measured in the absence of shear (5). In that study, an ␣ 4 tail mutant, Y991A, with disrupted binding to paxillin and reduced recruitment of talin 1 to the ␤ 1 subunit of the integrin heterodimer, exhibited reduced VLA-4 adhesiveness to VCAM-1 measured under shear stress conditions (5).…”
Section: Vla-4 (␣mentioning
confidence: 87%
See 2 more Smart Citations
“…Specific cytoskeletal partners of integrins may therefore regulate not only the affinity and clustering states of their integrin targets but also the efficiency by which an integrin occupied with ligand can strengthen its bond under the influence of external forces. In support of this possibility, we recently showed that the adhesive activity under shear of the key immune cell integrin, VLA-4, is modulated by an ␣ 4 cytoplasmic association with paxillin, without any noticeable changes in its affinity, clustering, or binding avidity to VCAM-1 2 measured in the absence of shear (5). In that study, an ␣ 4 tail mutant, Y991A, with disrupted binding to paxillin and reduced recruitment of talin 1 to the ␤ 1 subunit of the integrin heterodimer, exhibited reduced VLA-4 adhesiveness to VCAM-1 measured under shear stress conditions (5).…”
Section: Vla-4 (␣mentioning
confidence: 87%
“…In support of this possibility, we recently showed that the adhesive activity under shear of the key immune cell integrin, VLA-4, is modulated by an ␣ 4 cytoplasmic association with paxillin, without any noticeable changes in its affinity, clustering, or binding avidity to VCAM-1 2 measured in the absence of shear (5). In that study, an ␣ 4 tail mutant, Y991A, with disrupted binding to paxillin and reduced recruitment of talin 1 to the ␤ 1 subunit of the integrin heterodimer, exhibited reduced VLA-4 adhesiveness to VCAM-1 measured under shear stress conditions (5). Since the adhesive defect of the integrin mutant could result from impairments in both paxillin and talin associations with the VLA-4 heterodimer, the specific contribution of each of these two key cytoskeletal integrin linkers to stabilization of VLA-4-VCAM-1 interactions under shear flow remained obscure.…”
Section: Vla-4 (␣mentioning
confidence: 87%
See 1 more Smart Citation
“…However, it is established that different integrin heterodimers expressed by the same cells can utilize distinct signaling components and downstream effectors. For example, paxillin binding to ␣4 integrin cytoplasmic domains is known to regulate cytoskeletal association and resistance to shear stress but not affinity of ␣4␤1, whereas paxillin does not bind to ␣L of LFA-1 (5,30,45).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that antibody cross-linking of ␣4 integrin on Jurkat cells leads to a significant increase in the amount of anti-␣4 mAb able to resist solubilization by a non-ionic detergent, and this is interpreted to result from an increase in ␣4 integrin association with the cytoskeleton (30). The association of ␤1 integrin with the cytoskeleton after activation by cross-linking of an anti-␤1 mAb was measured.…”
Section: Sorafenib Inhibits Cell Spreading and ␤1 Integrin Colocalizamentioning
confidence: 99%